Intimate Partner Violence Against Asian American Women: Moving From Theory to Strategy - Lee, Donna H. (Columbia Journal of Gender and Law, 2014)
Despite theoretical advances in understanding intimate partner violence (1P V), practical strategies for addressing the destruction it wreaks on individuals, families, and communities have stagnated. Criminal prosecutions of domestic violence, legal services to help IPV survivors obtain civil orders of protection, emergency shelters, and social services counseling provide help, but fall short. Examining social science data through an intersectional lens, this Article generates new approaches that are tailored to a specific demographic group: Asian American women. Analysis of the research done by social workers, sociologists, psychologists, and organizers about the experiences of Asian American IPV survivors yields three conceptualframes: individual, situational, and structural. I use these frames to construct and support specific proposals for working with women who choose to stay with their abusive partners, and for effecting systemic change in state court systems.